Shariah governance practices of Malaysian Islamic banks in the light of Shariah compliance - Rosnia Masruki,; Mustafa Mohd Hanefah,; Bablu Kumar Dhar, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Islamic banks in Malaysia must conform to Shariah rules in their operations. Islam’s prohibition of usury is the main justification for the necessity of Islamic banks (IBs). Indeed, the implementation of Shariah governance through the Shariah Supervisory Board (SSB) is essential to monitor and govern the operations of IBs for ensuring the integrity, credibility and transparency of IBs. Failure to conform to good Shariah governance practices will result in the IBs’ failure to uphold Shariah in their operations. The objective of this paper is to examine the Shariah governance practices of IBs in Malaysia. This study employs content analysis to identify the extent to which the Shariah governance is being practised by IBs. A disclosure checklist was developed based on a review of previous studies and regulations, namely the Guidelines of Financial Reporting for Islamic Financial Institutions (GP8-i) 2005, Islamic Financial Services Act (IFSA) 2013 and Shariah Governance Framework (SGF) 2010 and Exposure Draft of SGF 2017. It consists of five dimensions: i) Shariah Committee; three control functions under Shariah governance, ii) Shariah Risk Management, iii) Shariah Review, iv) Shariah Audit and v) Transparency and Disclosure. The findings suggest that IBs were more likely to disclose Shariah committee attributes, whereas Shariah control function items (Shariah risk management, Shariah review, Shariah audit) and transparency and disclosure were less likely to be disclosed, indicating that IBs seem to be heavily dependent on the competency of SSB members rather than the Shariah compliance mechanisms. This study contributes to the interest of IBs and the Shariah Committee themselves to consider various mechanisms of Shariah governance practices to garner trust and confidence of a wide range of stakeholders. Future studies can be carried out to suggest best practices of Shariah compliance mechanisms in relation to the SGF issued by the Central Bank of Malaysia.